Perancangan UX (User Experience) Sistem Informasi Lifeskill Menggunakan Metode UCD di Universitas Muhammadiyah Kalimantan Timur (UMKT) - Bulan Suci Cahayawati; Naufal Azmi Verdikha; Muhamad Wahyu Tirta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The development of information technology is important, especially in the field of education, in supporting the learning process for the better. Muhammadiyah University of East Kalimantan, which carries the IT Based Paperless concept, is one of the campuses that supports the development of information technology. SI Lifeskills was introduced to record and integrate the development of students' academic achievements, where this system helps Life Skills courses to be more organized and effective. The system development demand was carried out in order to increase needs, especially in terms of user experience (UX). This service is carried out as a form of activity to increase comfort in learning services using a User Centered Design (UCD) approach. The evaluation stages carried out in this research used Heuristic Evaluation with 10 parameter aspects. The Heuristic Evaluation test results obtained Severity Ratings 0 with 8 points and Severity Ratings 1 with 2 points. The evaluation results show that the system is comfortable to use with problems that have minimal impact on the user so that repairs are not needed if time is limited.